A performance modeling framework for energy-based scheduling in cloud - Hussin, Masnida; Raja Mahmood, Raja Azlina; Husin, Nor Azura; Mohd Norowi, Noris (Society of Digital Information and Wireless Communications (SDIWC), 2015)
Cloud computing becomes a powerful trend in the development of ICT services. Cloud providers typically try to provide high performance to their users while minimizing energy consumption in their operation. However, there is lack of performance metric that analyzing trade-off between performance and energy consumption. Considering high volume of mixed users’ requirements and diversity of services offered; an appropriate performance model for achieving better balance between Cloud performance and energy consumption is needed. One of resource management strategies for better performance is through effective scheduling approach. In this paper we investigate a relationship between performance metrics that chosen in existing scheduling approaches with energy consumption for energy efficiency. Through such relationship, we develop an energy-based performance modeling framework that provides a clear picture on parameter selection strategy for effective energy management. Our framework provides adaptive guideline for designing performance model explicitly for energy efficient scheduling. We believed that better understanding on how to model the scheduling performance will lead to green Cloud computing.